2013
DOI: 10.1515/text-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

The structure of emotion discourse: from Labovian to socio-cognitive models

Abstract: This paper focuses on how narrators convey emotion in the structure of oral narrative discourse in Spanish. To this end, the structure of personal oral narratives of highly emotional events in a sample of radio narratives is analyzed from two different approaches: Labovian and socio-cognitive. This work shows, first, how the Labovian approach to personal oral narratives of "vivid" events is applied to emotionally charged texts and, second, how the theoretical concepts of mental spaces and conceptual integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…However, even though studies in both emotion psychology and linguistic research have shown that language plays an important role in conceptualising and understanding emotions (see Niemeier & Dirven, 1997;Fussel, 2002;Gendron, 2012), only very few studies have focused on a linguistic analysis of emotion terms (e.g. Halliday, 1998;Weigand, 2004;Bednarek, 2008;Romano et al, 2013), let alone the emotion anger. Consequently, it is necessary and worthwhile to analyse emotional or affective expressions from a linguistic perspective, which could contribute to bettering our understanding of emotions and further assisting emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, even though studies in both emotion psychology and linguistic research have shown that language plays an important role in conceptualising and understanding emotions (see Niemeier & Dirven, 1997;Fussel, 2002;Gendron, 2012), only very few studies have focused on a linguistic analysis of emotion terms (e.g. Halliday, 1998;Weigand, 2004;Bednarek, 2008;Romano et al, 2013), let alone the emotion anger. Consequently, it is necessary and worthwhile to analyse emotional or affective expressions from a linguistic perspective, which could contribute to bettering our understanding of emotions and further assisting emotion regulation.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Meta-narratives are also termed grand narratives (Lyotard, 1984), frames (Fligstein, Brundage, and Schultz, 2017), narrative templates (Wertsch, 2008), generic space (Romano, Porto, and Molina, 2013: 85), or deep stories (Hochschild, 2016; Polletta and Callahan, 2017). …”
mentioning
confidence: 99%
“…The last chapter, by Rodríguez Redondo, analyses gesture structuring strategies in autobiographical narratives, also contrasting Spanish and English data. Her study is based on recent perspectives on the conceptual segmentation of oral emotional narratives (Romano & Porto, 2010; Romano, Porto, & Molina, 2013), and the development of cognitive gesture studies (McNeill, 1992, among others). However, her main purpose is to obtain upgraded tools focusing on gestures as meaning-making helpers through a given discourse.…”
mentioning
confidence: 99%